Simultaneous mutually exclusive active tubercular posterior uveitis - Ramanjulu, Rajesh (Indian J Ophthalmol, 2020)
Ocular tuberculosis (TB) is a form of extra-pulmonary TB, which can involve almost any intraocular structure or ocular adnexa. Posterior uveitis, the commonest form of intraocular TB manifests as choroidal tubercles, choroidal tuberculoma, subretinal abscess, neuroretinitis, or serpiginous-like choroiditis. These forms of posterior tubercular lesions can be broadly classified into two groups based on their pathophysiology and morphology. One group of lesions is related to the direct invasion and reactivation of the bacilli in the choroidal tissue, whereas the other is a result of hypersensitivity reaction to the bacilli. Simultaneous bilateral active posterior uveitis with such varying morphology and pathophysiology in either eye of the same patient is an extremely rare presentation. We report a case with pulmonary TB on Anti-tubercular therapy (ATT), who presented to us with two mutually exclusive and distinctly different forms of tubercular posterior uveitis in either eye simultaneously. Both lesions were active at the time of presentation.